Post-merger Employee Satisfaction in Commercial Banks of Nepal: Findings from Employee Satisfaction Index - Shrestha, Eliza; Devkota, Niranjan; Paudel, Uday R; Parajuli, Seeprata (Journal of Business and Social Sciences Research, 2021)
Various mergers and acquisitions started in in Nepalese banking sector, since 2011 when Nepal Rastra Bank issued the merger by-law. This paper, therefore, aims to explore post-merger employee satisfaction of commercial banks in Nepal. Employees of Nepalese commercial banks are considered as population of the study. Hence, the sample of 310 commercial bankers is taken for the study. Result of the study revealed that employees of commercial banks (50 percent) are moderately satisfied, and post-merger and lack of effective communication were found to be the major challenges faced by most (65.16 percent) of the employees. However, 23 percent of the employees believed that if they were provided with proper training and development opportunities, they could mitigate challenges arising from post-merger activities. Therefore, the study concludes that banks should identify needs of employees and provide such an environment where they can work flexibly in the post[1]merger period.